A Digest of the Laws of Pennsylvania: From the Year One Thousand Seven Hundred to the Sixth Day of July, One Thousand Eight Hundred and Eighty-Three, at 423-24, Crimes, pt. 6, § 113 (11th ed., Vol. 1, 1885) - (:unkn) unknown (General Publisher, 1883)
Any person who shall knowingly and willfully sell or cause to be sold to any person under sixteen years of age, any cannon, revolver, pistol or other such deadly weapon, or who shall knowingly and willfully sell, or cause to be sold, to any such minor, any imitation or toy cannon, revolver or pistol so made, constructed or arranged as to be capable of being loaded with gunpowder or other explosive substance, cartridges, shot, slugs or balls and being exploded, fired off and discharged, and thereby become a dangerous or deadly weapon, or who shall knowingly and willfully sell, or cause to be sold to any such minor, any cartridge, gunpowder or other dangerous and explosive substance, shall in every such case, be guilty of a misdemeanor, and upon conviction thereof shall be sentenced to pay a fine not exceeding three hundred dollars.
--
Keywords: TRANSFER - MINORS